Spectroscopic twin to the hypervelocity sdO star US 708 and three fast sdB stars from the Hyper-MUCHFUSS project - Ziegerer, Eva; Heber, Ulrich; Geier, Stephan; Irrgang, Andreas; Kupfer, Thomas; Fuerst, F.; Schaffenroth, Johannes (Astronomy & Astrophysics, 2017)
Important tracers for the dark matter halo of the Galaxy are hypervelocity stars (HVSs), which are faster than the local escape velocity of the Galaxy and their slower counterparts, the high-velocity stars in the Galactic halo. Such HVSs are believed to be ejected from the Galactic centre (GC) through tidal disruption of a binary by the super-massive black hole (Hills mechanism). The Hyper-MUCHFUSS survey aims at finding high-velocity potentially unbound hot subdwarf stars. We present the spectroscopic and kinematical analyses of a He-sdO as well as three candidates among the sdB stars using optical Keck/ESI and VLT (X-shooter, FORS) spectroscopy. Proper motions are determined by combining positions from early-epoch photographic plates with those derived from modern digital sky surveys. The Galactic rest frame velocities range from 203 km s(-1) to 660 km s(-1), indicating that most likely all four stars are gravitationally bound to the Galaxy. With T-eff = 47 000 K and a surface gravity of log g = 5 : 7, SDSS J205030.39-061957.8 (J2050) is a spectroscopic twin of the hypervelocity He-sdO US 708. As for the latter, the GC is excluded as a place of origin based on the kinematic analysis. Hence, the Hills mechanism can be excluded for J2050. The ejection velocity is much more moderate (385 +/- 79 km s(-1)) than that of US 708 (998 +/- 68 km s(-1)). The binary thermonuclear supernova scenario suggested for US 708 would explain the observed properties of J2050 very well without pushing the model parameters to their extreme limits, as required for US 708. Accordingly, the star would be the surviving donor of a type Ia supernova. Three sdB stars also showed extreme kinematics; one could be a HVS ejected from the GC, whereas the other two could be ejected from the Galactic disk through the binary supernova mechanism. Alternatively, they might be extreme halo stars.
Keywords: stars: kinematics and dynamics; subdwarfs; stars: atmospheres; Galaxy: halo